Teacher Emotions and Teacher Self-Regulation: Insights from Teachers’ Perspectives - Yurtseven, Nihal; Saraç, Seda (International Electronic Journal of Elementary Education, 2024)
In this paper, we aimed to explore the connection between teacher emotion and self-regulation, the predictive power of teacher emotions on teacher self-regulation, and factors that influence teachers’ emotions. An exploratory sequential design was adopted in the study. Data was gathered from 403 teachers teaching actively in elementary grades in the quantitative dimension. In the qualitative dimension, a focus group interview was held with eight teachers. The Teacher Emotion Questionnaire (TEQ), The Teacher Self-Regulation Scale, and focus group interview questions were used to collect data. The quantitative data was analyzed through correlational analysis and simple linear regression analysis and the qualitative data was analyzed through content analysis. The quantitative findings demonstrated that teachers' pride and love in the profession significantly predicted teacher self-regulation levels; however, predicted only 2% of the variability in teacher self-regulation. The findings from the qualitative dimension seemed to explain why we did not find significant relationships between teacher self-regulation and teacher emotions. Emotions seem to be unrelated to teaching skills. Instead, the teachers attribute the source of their emotions mostly to external factors and individual characteristics to some extent.